“Diseño de un canal hidraúlico de pendiente variable”. - Quinaluisa Chicaiza, Estalin Adrián (2023)
The technological proposal is based on the design and construction of a hydraulic channel of variable slope, which is intended to provide support to students and teachers in carrying out research practices in the hydraulics laboratory to study physical phenomena of flow, hydraulic jumps by landfills etc